Study on possibility to determine jaundice symptom using vision system - Sakinah, Mazlan (2016)
Jaundice is one of the most common disease affecting neonates worldwide caused by hyperbilirubinaemia in blood, which results in the appearance of yellow discolouration forming on the skin & white eyes (sclera). In the rise in today’s technology, apparently one of the most popular methods used in our country used for detection and confirming the symptoms is by blood sampling and other clinical testing with special equipment. But the main issue here is the blood sampling as it seems to be a bit painful especially for infants who are mostly less than 30 days old. One of the non-invasive methods is by measuring the level of bilirubin in blood using a bilirubinometer. It is a small accurate device which uses spectrophotometry but this small device has a really steep price tag, around $500 - $2000 a unit. So, the aim of this study is creating an affordable non-invasive system to determine whether a person is jaundice patient by detecting the yellow component on the skin using vision system. Throughout the progress, around 19 pictures of various samples (13 jaundiced & 6 healthy) were taken and colour analysis (RGB) was done on each samples in a software (MatLab). From the colour spaces mentioned, the mean values of each component were calculated and used to plot a distribution graph. Then, the graphs were observed to differentiate any obvious trends happening between the healthy and jaundiced samples. From RGB graph, yellow component is extracted from Green - Blue component and all 13 jaundiced samples shows higher yellow component than the healthy samples. A graphical user interface (GUI) is used to give a clearer view and better understanding for the audience.